FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN BPR RANAU TENGAH - Suci Indah Permata Sari; Bainil Yulina; Evada Dewata (KRISNA: Kumpulan Riset Akuntansi, 2026)
The purpose of this study is to examine how the accountability of village fund management in the BPR Ranau Tengah District, OKU Selatan Regency, is impacted by the role of village authorities, the clarity of budget targets, the use of information technology, and the internal control system. The research was motivated by persistent issues of mismanagement and lack of transparency in village fund allocation despite regulatory frameworks. Using a quantitative method, 63 village authorities from 21 communities filled out questionnaires, which were sent out using a saturated sampling method. To analyse the data, this study employs validity tests, traditional assumption tests, and hypothesis tests. Only the role of village authorities has a beneficial impact on accountability, according to the research findings. However, the use of technology, internal control systems, and the clarity of budget targets have little effect. These results show that the active participation and dedication of village leaders have a bigger effect on accountability than technical systems alone. The study helps improve village fund governance in real-life applications and provides a deeper understanding of how to apply stewardship theory in managing public funds.